2022
DOI: 10.3389/fmicb.2022.844962
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microbial Community and Metabolites in Four Stomach Compartments of Myostatin-Gene-Edited and Non-edited Cattle

Abstract: Myostatin (MSTN), a major negative regulator of skeletal muscle mass and an endocrine factor, can regulate the metabolism of various organisms. Inhibition of the MSTN gene can improve meat production from livestock. Rumen microorganisms are associated with production and health traits of cattle, but changes in the microbial composition and metabolome in the four stomach compartments of MSTN gene–edited cattle have not previously been studied. Our results indicated that microbial diversity and dominant bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The glucose level of MT cattle was significantly lower than that of WT cattle, while the lipase, urea, lactic acid, and amylase activity of MT cattle were significantly higher, which suggests that mutation of the MSTN gene changed the metabolism of glucose, lipids, and proteins. Our most recent reports showed that MSTN gene mutation in cattle induced complex and elaborate mechanisms to skeletal muscle, heart muscle, stomach microbe, and bile acid metabolism [ 19 , 36 , 37 , 38 ]. The biological significances of the changes in biochemical parameters need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glucose level of MT cattle was significantly lower than that of WT cattle, while the lipase, urea, lactic acid, and amylase activity of MT cattle were significantly higher, which suggests that mutation of the MSTN gene changed the metabolism of glucose, lipids, and proteins. Our most recent reports showed that MSTN gene mutation in cattle induced complex and elaborate mechanisms to skeletal muscle, heart muscle, stomach microbe, and bile acid metabolism [ 19 , 36 , 37 , 38 ]. The biological significances of the changes in biochemical parameters need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports have shown that the glycolysis, glycogen metabolism, and fatty acid β-oxidation was significantly changed in MT cattle [ 37 , 46 , 47 , 48 ]. Meanwhile, various effects of MSTN gene mutation on cattle and the related molecule mechanism have been investigated, including bile acid metabolism [ 19 ], enhanced glycolysis in the heart [ 37 ], and microbial community of stomach [ 36 ]. The energy metabolism was changed in MT cattle, so the sperm mitochondria should be also affected.…”
Section: Discussionmentioning
confidence: 99%
“…The generated MSTN -edited cattle were employed in further comparative investigations, including transcriptomic, , proteomic, , metabolomic, , and microbial , analyses. These comparative analyses provided lists of genes and pathways that potentially contribute to the emergence of the double-muscling phenotype in MSTN -edited cattle.…”
Section: Targeting the Mstn Gene In Cattlementioning
confidence: 99%
“…36 This could likely contribute to the generation of improved muscle mass by targeting the MSTN gene and potential resistance to prion infection by editing the PRNP gene. 37 The generated MSTN-edited cattle were employed in further comparative investigations, including transcriptomic, 38,39 proteomic, 35,40−42 metabolomic, 43,44 and microbial 45,46 analyses. These comparative analyses provided lists of genes and pathways that potentially contribute to the emergence of the double-muscling phenotype in MSTN-edited cattle.…”
Section: ■ Targeting the Mstn Gene In Cattlementioning
confidence: 99%
“…Luxi cattle with the MSTN gene mutations prepared by the Inner Mongolia University through the clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/CAS9) technology have more developed muscles and a higher lean meat yield ( 9 ). Previous studies had analyzed the changes in gut bacteria composition in MSTN -mutated cattle and found that the MSTN mutation affects the metabolism of the body by regulating the composition of gut bacteria, thereby affecting the growth traits of beef cattle ( 10 , 11 ). However, there are no reports on the changes in MSTN mutant bovine gut fungi and their correlation with host metabolism.…”
Section: Introductionmentioning
confidence: 99%